Wizytacje kanoniczne i dziekańskie w archidiecezji lwowskiej obrządku łacińskiego do 1939 roku - Leszczyński, Mariusz (Archiwa, Biblioteki i Muzea Kościelne, 2020)
One of the important duties of the rulers of a diocese was to conduct canonical visitations in parishes (visitatio canonica, visitatio pastoralis). According to the recommendations of the Council of Trent (1545-1563), suffragan bishops (assistant) were supposed to help them in this duty. Detailed standards for the canonical visitations of parishes in the 20thy century were included in the Code of Canon Law of 1917. They said, among other things, that every year the “residential” bishop should visit his diocese or part of it so that to visit at least one parish every five years. He was supposed to perform this task in person or-in case of a reasonable obstacle-by a vicar general, or by another clergyman. Bishops conducted visitation of people, things and pious establishments, apart from the ones which received a special exemption from the Holy See. The practice of canonical and deanery visitations in the Archdiocese of Lviv of the Latin rite varied over the centuries. Regular visitations were conducted, for example by Archbishop Wacław Hieronim Sierakowski (1760-1780) and Józef Bilczewski (1900-1923). Archbishop Seweryn Tytus Morawski (1885-1900) did not conduct any visitations in person, he would entrust this task to the assistant bishop or other clergymen. Deanery visitations were closely connected with canonical ones; and they were especially important when canonical visitations were not conducted regularly. The aim of deanery and canonical visitations was to recognise the condition and the needs of the parish and to control the implementation of ecclesiastical law and other ordinances of ecclesiastical authorities.